Exon 9 of Vitamin D Receptor Association with Occult Hepatitis B Virus Infection - M Kazemi Arababadi (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Immune system is unable to complete clearance of hepatitis B virus in occult hepatitis B infection (OBI). Some of immune response is defect against hepatitis B virus in these patients. Scientists believed the involvement of genetic and immunological factors in etiology of OBI. Due to the regulatory impact of vitamin D3 on immune system, study of vitamin D receptor (VDR) polymorphisms aid to better understanding of disease. Therefore, in this study we examined exon 9 polymorphisms of VDR in OBI patients.METHODS: In this experimental study, 3700 samples were examined for anti-HBc and HBsAg by ELISA. The HBsAg negative and anti-HBc positive samples were screened for HBV-DNA by PCR. OBI patients (57 cases) (HBsAg negative and anti-HBc positive, HBV-DNA positive) and 100 healthy controls (HBsAg negative and anti-HBc positive, HBV-DNA negative) were analyzed for exon 9 polymorphisms of VDR by PCR-RFLP techniques. FINDINGS: Our findings demonstrated that 57 cases had OBI among 3700 studied cases. Polymorphisms analysis showed that 3.5% (2 cases) of OBI patients and 18% (18 cases) of controls had T/T alleles in this region which the difference was statistically significant in patients and controls (p<0.049). There was not also a significant difference between OBI patients and controls regarding T/t and t/t alleles of this region of VDR. CONCLUSION: Regarding results of this study we can be concluded that the T/T allele in exon 9 of VDR may play key role in ability of immune system in clearance of HBV in OBI patients.